2017
DOI: 10.3168/jds.2017-12785
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile of goat milk in diets supplemented with chia seed (Salvia hispanica L.)

Abstract: Chia seed (Salvia hispanica L.) is the greatest known plant source of n-3 α-linolenic acid. The present study evaluated the effects of 3 inclusion levels of chia seed [zero (control); low, 2.7% (CLow); and high, 5.5% (CHigh)] in diets of dairy goats on milk yield and fatty acid profile. Nine Saanen dairy goats in the last third of lactation period, live weight 38 ± 8.7 kg, housed in metabolic cages, were fed iso-proteic and iso-energetic (160 g of crude protein/d and 11 MJ of metabolizable energy/d) diets. Gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 49 publications
1
19
0
2
Order By: Relevance
“…Many studies demonstrated that even small amounts of chia seeds in animal diets can dramatically improve the omega-3 content of eggs [11,19,73] and of poultry and lamb meat [12,74]. Nevertheless, data on lactating goats fed with chia seeds [13] show that the FA profile of milk is improved but that ALA undergoes a substantial biohydrogenation in the rumen. The effect of including chia forage in the diet of ruminants remains to be ascertained, but it is possible that leaf antioxidants would play a role in protecting polyunsaturated fatty acids (PUFA).…”
Section: Forage Qualitymentioning
confidence: 99%
“…Many studies demonstrated that even small amounts of chia seeds in animal diets can dramatically improve the omega-3 content of eggs [11,19,73] and of poultry and lamb meat [12,74]. Nevertheless, data on lactating goats fed with chia seeds [13] show that the FA profile of milk is improved but that ALA undergoes a substantial biohydrogenation in the rumen. The effect of including chia forage in the diet of ruminants remains to be ascertained, but it is possible that leaf antioxidants would play a role in protecting polyunsaturated fatty acids (PUFA).…”
Section: Forage Qualitymentioning
confidence: 99%
“…In particular, in all samples α-linolenic acid represented > 49% of the total fatty acids fraction, being this compound an essential omega-3 polyunsaturated fatty acid. This fatty acid is defined as a fundamental factor for brain and visual function in humans (Sakayori et al, 2016), and its deficiency could led to many health problems, because it cannot be synthesized in humans, therefore it must be supplied through the diet (Schettino et al, 2017). For tocopherols composition, wild cardoon presented all the different isoforms of tocopherol (α-, β-, γand δ) and, as expected, the highest amount of total tocopherol (9.6 ± 0.1 mg/100 g dw), being δtocopherol the most abundant isoform followed by γ-tocopherol (2.8 ± 0.1 and 2.36 ± 0.01 mg/100 g dw, respectively).…”
Section: Turnipmentioning
confidence: 99%
“…Among these fatty acids, Oleic acid (C18:1n9c) was the most abundant fatty acid (1,536.12 ± 0.12) in untreated samples, followed by Palmitic acid (C16:0) (1,048.38 ± 0.14) and Stearic acid (C18:0) (809.13 ± 0.11). The prominent Oleic acid (C18:1n9c) content was partly correlated to the biohydrogenation process in the goat milk fatty acid like Linoleic acid (Schettino et al, 2017). Individual SFA including Butyric, Caproic, Caprylic, Capric, Lauric, Myristic, Pentadecanoic, and Palmitic acid were found slightly changed ( p > .05) than those in the untreated sample.…”
Section: Resultsmentioning
confidence: 99%
“…and Stearic acid (C18:0) (809.13 ± 0.11). The prominent Oleic acid (C18:1n9c) content was partly correlated to the biohydrogenation process in the goat milk fatty acid like Linoleic acid (Schettino et al, 2017 (Lopez et al, 2019). The position of fatty acid in the triacylglycerols determines their rate of oxidations (Ghnimi et al, 2017).…”
Section: Effect On Fatty Acid Profilingmentioning
confidence: 99%